Effect of Kombucha Tea on Total Cholesterol Decreasing Levels in White Rats (Rattus norvegicus) - Zulkifli Halid; Sulaiman Sulaiman; Rifka Irhamna (Universitas Islam Negeri Alauddin Makassar, 2021)
The purpose of this study was to determine the type of content of 75% kombucha tea that is fermented for 12 days, there are black tea, green tea, and the packaged tea. Fifteen Rattus norvegicus was randomized divided into 5 groups and each group consisted of 3 rats. Group I or the negative control was given aquadest, group II was given kombucha packaged tea, group III was given black tea kombucha, and group IV was given green tea kombucha. Group V as a positive control was given simvastatin. All groups were injected with the samples solution orally. Evaluation of effects was carried out by observed the cholesterol total level before and after treatment. The results showed that all kombucha tea can reduced the total cholesterol level on rats (Rattus norvegicus). Conclusion: Data were analyzed using ANOVA followed by Duncan test with 95% confidence level using SPSS 20.0 software, results showed that black tea kombucha 1.8 mL of 75% concentration has an optimal reduced total cholesterol levels in rats (Rattus norvegicus).